All in One: A Comprehensive Goal and Indicator System for Smart Bioenergy. Issue 8 (26th June 2020) - Szarka, Nora; Schmid, Christopher; Pfeiffer, Diana; Thrän, Daniela
Abstract: Owing to the increasing challenges of climate change and limited resources, a bundle of requirements for bioenergy are given, such as securing the energy supply, linking with the material use of biomass, or producing negative emissions. Smart bioenergy generation and utilization can fulfil those requirements by the sustainable, efficient, and flexible provision of renewable energy. This study aims to thoroughly define and structure all contributions bioenergy can make to the energy system, in the form of a comprehensive multilevel goal and indicator system. The built system includes several levels of subgoals associated with biomass, with technology, and its integration. The goal system was verified by research project leaders and further experts and can be applied to any bioenergy concept worldwide. Abstract : All contributions offered by bioenergy to support a secure, efficient, and sustainable energy system are thoroughly defined and structured. A comprehensive multilevel bioenergy goal and indicator system was developed, representing goals regarding biomass, the related technology and its integration. The developed system was verified by several experts and can be applied to any bioenergy concept.